Narratives by students of LGBTQ+ community in the space of the Federal University of Piauí: tensions and upheavals - dos Santos Sousa, Claudiane; Maria Mendes Marques, Marcia; Neto Fonseca Duque, Adauto; Veloso, Caio; Masciel Neiva Gonçalves, Nilda (Seven Editora, 2023)
This article presents an analysis of the narratives by students at the Federal University of Piauí/Campus Senador Helvídio Nunes de Barros belonging to the LGBTQ+ community, pointing out the tensions and upheavals suffered by because of their sexual orientation. The research followed the qualitative approach and the interpretative analysis of the students' narratives allowed us to identify the possible tensions and upheavals they feel at university. The UFPI/CSHNB emerges as a plural and diverse space, where the student feels free to be himself and to be in the world. A space of encounters and comfort, of overcoming and absence of judgment of sexual orientation. We did not find in the students' narratives tensions or upheavals in their initial training that had a negative impact. But on the other hand, we found tensions related to self-knowledge and family acceptance, as well as upheavals related to their insertion in the labor market. The text presents subsidies for further discussion and analysis of the context of the formation of individuals belonging to the LGBTQ+ community. DOI: 10.56238/pacfdnsv1-011